PENDIDIKAN KARAKTER DALAM VISUALISASI DAN MAKNA FILOSOFIS MOTIF BATIK LEGENDA BULUSAN - Vania Febianti; Eko Sugiarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesian batik has been recognized by UNESCO as an intangible cultural heritage since 2009. Kudus batik is one of the local cultural heritages rich in meaning. The meaning contained in batik motifs can function as a learning medium and educational tool for the wider community. The Bulusan Legend motif contains cultural, philosophical, and character-education values that reflect the folklore of Hadipolo village, Kudus Regency. This study aims to analyze the visualization of the motif, philosophical meaning, and character values ​​contained in the Bulusan Legend batik. The research method uses a descriptive qualitative method. Research data were collected through observation, interviews, and documentation. The results of the study are as follows: first, in terms of visualization, the Bulusan Legend batik features many elements arranged according to folklore. The main elements displayed are those of trees, turtles, and human figures, along with supporting elements such as rocks, clouds, rivers, and grass. Second, the philosophy of the Bulusan Legend motif represents local wisdom values ​​such as obedience, humility, and respect. Third, the Bulusan Legend batik motif can also be used as a means of character education, instilling positive values in the younger generation within the context of education and cultural preservation. The character traits include religious values, cooperation, responsibility, and social awareness. The research suggests developing batik-based educational programs in schools